Versatile On-Board Power Processor for BLDC & IM Driven Electric Vehicles - Maurya V.P.; Singh R.K. (My University, 2025)
This paper proposes a versatile on-board power converter for BLDC and induction motor-driven electric vehicles. The single converter can be operated in charging as well as in motoring mode of operation. The proposed converter transforms between charging and propulsion operation with the help of electromechanical relays and some passive components. In its charging operation, it maintains the unity power factor at the source terminal and charges the battery with a constant current constant voltage (CC-CV) algorithm. In its propulsion operation, it can drive either the brushless DC motor or the Induction motor with different switching logic. It provides the source voltages to the power support of the cabin in charging and propulsion operation. The concept is validated for 300 W and 500 W during charging and motoring mode, respectively. © 2023 IEEE.